Piesc boga - Forsyth, Frederick, 1938- (Warszawa : Wydawnictwo Amber, 1994)
Polish translation of Frederick Forsyth's novel during the Persian Gulf War, "The Fist of God."
Translation of: The fist of God.
Keywords: Persian Gulf War, 1991 -- Fiction